MENJAUHI BUDAYA BIROKRASI BERWATAK TRADISIONAL - Andi Ali Said Akbar (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
This article will build an argument that the appearance of the bureaucratic apparatus which is very easy to practical political involvement, collusion, corruption and nepotism, not just a symptom of mental damage to the individual body but rather a mirror of government bureaucracy cultural mutation traditionalist character of aristocracy, politicians and corporate governance into the modern. First, the aristocratic culture of bureaucracy become the seedbed of power-managed hereditary kinship-based culture. Second, the political culture. Bureaucracy does not become a public servant but a political machine tradisonalnya succession due to the position as a social elite and technocrats modernya position of authority. Third, the corporate culture. Bureaucracy appears as a corporation as a form of political incentives to material interests. Construction of this bureaucratic culture could not be amputated just “oknumisasi” method. Reinstitusionalisasi bureaucracy should be started the Constitutional aspect, institutions, education, operationalization to strengthening public access to and control of the governmental process. This framework will be able to create an effective bureaucracy, responsible and constructive way to democratization.